2016
DOI: 10.1007/s40097-016-0210-5
|View full text |Cite
|
Sign up to set email alerts
|

Fine fibrillar and rectangular/hexagonal ordered grains of poly(3-hexyl thiophene) and poly(ethylene glycol) developed by seeding technique

Abstract: The fibrillar poly(3-hexyl thiophene) single crystals were prepared from dilute solutions of toluene, xylene, and anisole (0.01 wt%), and were investigated from the perspective of structural properties. Next, the rectangular and hexagonal poly(ethylene glycol) single crystals were developed from the dilute solutions and molten thin polymer films. The developing methodology used for all growth systems was self-seeding. The dimensions of fibrillar and rectangular/hexagonal single crystals ranged from several nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…Therefore, only the spots associated with [120] growth fronts of PEG were detected in SAED patterns. This was similar to results reported in the literature , …”
Section: Resultssupporting
confidence: 93%
“…Therefore, only the spots associated with [120] growth fronts of PEG were detected in SAED patterns. This was similar to results reported in the literature , …”
Section: Resultssupporting
confidence: 93%
“…Among the conjugated polymers, regioregular P3HT (RR‐P3HT), thanks to appropriate processability and electrical properties, good function and a marked tendency to develop nanostructured crystals, is one of the attractive materials in electronic devices . The manipulation of the physical, thermal and optical characteristics of P3HT based systems and their application in photovoltaic cells has been reported in the literature. In organic solar cells, block copolymer compatibilizers were utilized to tune the active layer morphology .…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that for the conjugated polymers like P3HT, the highest conductivity occurs along with the polymer backbone, and also through π–π stacking . The crystallinity of P3HT was investigated in different structures comprising the scrolled half‐ring crystals, the flat fibrillar nanofibers and single crystals, and stratified morphologies . The common orientations for the P3HT chains are the edge‐on (with the main backbones parallel with and side chains perpendicular to the substrate) and face‐on (with both main backbones and side chains parallel with the substrate).…”
Section: Introductionmentioning
confidence: 99%